DNA topoisomerases as molecular targets for anticancer drugs - Kamila Buzun; Anna Bielawska; Krzysztof Bielawski; Agnieszka Gornowicz (Taylor & Francis Group, 2020)
The significant role of topoisomerases in the control of DNA chain topology has been confirmed in numerous research conducted worldwide. The prevalence of these enzymes, as well as the key importance of topoisomerase in the proper functioning of cells, have made them the target of many scientific studies conducted all over the world. This article is a comprehensive review of knowledge about topoisomerases and their inhibitors collected over the years. Studies on the structure-activity relationship and molecular docking are one of the key elements driving drug development. In addition to information on molecular targets, this article contains details on the structure-activity relationship of described classes of compounds. Moreover, the work also includes details about the structure of the compounds that drive the mode of action of topoisomerase inhibitors. Finally, selected topoisomerases inhibitors at the stage of clinical trials and their potential application in the chemotherapy of various cancers are described.